Inkulturasi Prier Memperkaya Ekspresi Iman dengan Musik - Simon Arief Herdian Putra Tama (Jurnal Teologi (Journal of Theology), 2018)
Post-colonial studies present a critique that the Church cannot exist merely as an archaic relic of colonialism. To transform this poignant stereotype, the Church should engage an inculturation. As a man of the Church, Karl-Edmund Prier has been involved in the Churchs inculturation projects by placing himself in the middle of the tension between faith and culture. His major contribution is the inculturated liturgical music to enrich the local Churchs creedal expression. He initiated an inculturation process, representing the willingness of the universal to enter into the local, an effort done with humility and kenosis. Through his method, Prier endeavored to discover liturgical songs that were harmonious with the sitz im leben, local sense, and the cultural imagination of the national Indonesian government. His monumental work is Madah Bakti considered as a mimicry of Gotteslob. As a liturgical musical book of the Indonesian Church, it represents a mixture of western and Indonesian ethnic songs. The aim is to allow the faithful to experience the local Church collaborates with the universal Church. Prier conducts simultaneously two acts, holding the global locally and promoting the local globally.